Sleep‐like behavior and 24‐h rhythm disruption in the Tc1 mouse model of Down syndrome. (16th February 2015) - Heise, I.; Fisher, S. P.; Banks, G. T.; Wells, S.; Peirson, S. N.; Foster, R. G.; Nolan, P. M.
Abstract : Down syndrome is a common disorder associated with intellectual disability in humans. Among a variety of severe health problems, patients with Down syndrome exhibit disrupted sleep and abnormal 24‐h rest/activity patterns. The transchromosomic mouse model of Down syndrome, Tc1, is a trans‐species mouse model for Down syndrome, carrying most of human chromosome 21 in addition to the normal complement of mouse chromosomes and expresses many of the phenotypes characteristic of Down syndrome. To date, however, sleep and circadian rhythms have not been characterized in Tc1 mice. Using both circadian wheel‐running analysis and video‐based sleep scoring, we showed that these mice exhibited fragmented patterns of sleep‐like behaviour during the light phase of a 12:12‐h light/dark (LD) cycle with an extended period of continuous wakefulness at the beginning of the dark phase. Moreover, an acute light pulse during night‐time was less effective in inducing sleep‐like behaviour in Tc1 animals than in wild‐type controls. In wheel‐running analysis, free running in constant light (LL) or constant darkness (DD) showed no changes in the circadian period of Tc1 animals although they did express subtle behavioural differences including a reduction in total distance travelled on the wheel and differences in the acrophase of activity in LD and in DD. Our data confirm that Tc1 mice express sleep‐related phenotypes that are comparable with those seen in Down syndrome patients with moderate disruptions in rest/activity patterns and hyperactive episodes, while circadian period under constant lighting conditions is essentially unaffected. Abstract : Video analysis detects an extended period of wakefulness in Tc1 mice during early night (active phase).